CAKUPAN KOREKSI DATA STREAMING CORS GMU1 DENGAN MENGGUNAKAN RECEIVER GNSS LEICA VIVA GS08 - , IRFANI INDRA NUR R. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Today, GNSS technology develops rapidly, both in terms of observation method, observation efficiency, coordinate accuracy, as well as range. Starting from static method, kinematic observation method then was developed, then RTK UHF method and the latest one is RTK NTRIP. Today, CORS (Continually Operating Reference Station) has been developed, it is a reference station which operate continuously so that it able to be used as a reference in determining the position of GNSS in real-time as well as post-processing. One of the services provided by CORS is RTK NTRIP (Real Time Kinematic Networked Transport of RTCM via Internet Protocol) observation method. The definitive coordinates of this method can be determined in real time by sending GNSS data correction in RTCM (Radio Technical Commission for Maritime Service) format via internet. One of CORS stations in Indonesia is CORS GMU1 in the UGM Geodetic Engineering area and has actively works as a reference station which provides services for various positioning applications as well as GNSS technology-based navigation. The question now is how far data streaming service of CORS GMU1 can be given to rover and how accurate the coordinated produced by RTK NTRIP method measurement using Leica Viva GS08 receiver. This study used RTK NTRIP method by using Leica Viva GS08 device as rover. Observation specification was performed with mask angle of 100, recording interval of 5 seconds, observation time 5 minutes in every distance less than 0,25 km